Increased incidence and clinical picture of childhood narcolepsy following the 2009 H1N1 pandemic vaccination campaign in Finland. - Markku Partinen (Public Library of Science (PLoS), 2012)
Background Narcolepsy is a rare neurological sleep disorder especially in children who are younger than 10 years. In the beginning of 2010, an exceptionally large number of Finnish children suffered from an abrupt onset of excessive daytime sleepiness (EDS) and cataplexy. Therefore, we carried out a systematic analysis of the incidence of narcolepsy in Finland between the years 2002-2010. Methods All Finnish hospitals and sleep clinics were contacted to find out the incidence of narcolepsy in 2010. The national hospital discharge register from 2002 to 2009 was used as a reference. Findings Altogether 335 cases (all ages) of narcolepsy were diagnosed in Finland during 2002-2009 giving an annual incidence of 0.79 per 100,000 inhabitants (95% confidence interval 0.62-0.96). The average annual incidence among subjects under 17 years of age was 0.31 (0.12-0.51) per 100,000 inhabitants. In 2010, 54 children under age 17 were diagnosed with narcolepsy (5.3/100,000; 17-fold increase). Among adults ≥20 years of age the incidence rate in 2010 was 0.87/100,000, which equals that in 2002-2009. Thirty-four of the 54 children were HLA-typed, and they were all positive for narcolepsy risk allele DQB1*0602/DRB1*15. 50/54 children had received Pandemrix vaccination 0 to 242 days (median 42) before onset. All 50 had EDS with abnormal multiple sleep latency test (sleep latency <8 min and ≥2 sleep onset REM periods). The symptoms started abruptly. Forty-seven (94%) had cataplexy, which started at the same time or soon after the onset of EDS. Psychiatric symptoms were common. Otherwise the clinical picture was similar to that described in childhood narcolepsy. Interpretation A sudden increase in the incidence of abrupt childhood narcolepsy was observed in Finland in 2010. We consider it likely that Pandemrix vaccination contributed, perhaps together with other environmental factors, to this increase in genetically susceptible children.